2013
DOI: 10.1002/ieam.1414
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the sewage treatment plant model SimpleTreat: Applicability domain and data requirements

Abstract: SimpleTreat 3.1 is the sewage treatment plant (STP) model implemented in the European Union (EU) framework for the environmental risk assessment of chemicals. The model was originally designed for neutral hydrophobic chemicals, whereas many substances currently under regulatory scrutiny, are ionizable at environmental pH. Although the model has been adapted to describe ionization (SimpleTreat 3.1), the fate of organic ions is limited to the unbound aqueous phase, which seriously restricts the applicability dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…SimpleTreat 3.1 is recommended in regulatory environmental risk assessments of chemicals in home and personal care products, industrial chemicals (REACH) (EC ), biocides (Biocidal Products Regulation) (EC ) and pharmaceuticals (European Medicines Agency ). The model has been updated to incorporate new algorithms to improve the estimation of the partitioning behavior of ionizable chemicals, making it applicable to a wider range of substances (Franco et al this issue). SimpleTreat 3.1 is usually run with a basic input data set and due to its worst‐case parameterization, predictions tend to be conservative.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…SimpleTreat 3.1 is recommended in regulatory environmental risk assessments of chemicals in home and personal care products, industrial chemicals (REACH) (EC ), biocides (Biocidal Products Regulation) (EC ) and pharmaceuticals (European Medicines Agency ). The model has been updated to incorporate new algorithms to improve the estimation of the partitioning behavior of ionizable chemicals, making it applicable to a wider range of substances (Franco et al this issue). SimpleTreat 3.1 is usually run with a basic input data set and due to its worst‐case parameterization, predictions tend to be conservative.…”
Section: Introductionsupporting
confidence: 85%
“…SimpleTreat 3.1 is usually run with a basic input data set and due to its worst‐case parameterization, predictions tend to be conservative. Results of the evaluation study with 9 test chemicals, including neutral and ionizable substances, have shown that SimpleTreat underestimates the removal efficiency, in particular for readily and inherently biodegradable substances (Franco et al this issue), in agreement with previous observations (HERA ; Geerts et al ). The underestimation of removal efficiency is in most cases due to the default first‐order biotransformation rate constants, assigned based on the non‐numerical results of screening biodegradability tests (i.e., OECD 301 or OECD 302) and applied only to the fraction of chemical dissolved in water.…”
Section: Introductionsupporting
confidence: 85%
“…Consequently, models have also been developed for APIs in different ion classes (Dobbs et al, 1989, Franco et al, 2009, Franco et al, 2013, Franco and Trapp, 2008, Guo et al, 2004, Sabljic et al, 1995). Recent work by Sathyamoorthy and Ramsburg (2013) derived separate multivariate models to predict K d values (at the experimental pH used for the measurements) for uncharged, and positively and negatively charged APIs, and combined models for their whole dataset.…”
Section: Introductionmentioning
confidence: 99%
“…For TCS and CIP, this resulted from an underestimation of removal via sorption to sewage sludge. Accordingly, Franco et al (2013a) suggested using measured K d values as input to SimpleTreat, though neglecting the impact of different sorption potentials of neutral and ionized species.…”
Section: Fate In Wwtpmentioning
confidence: 99%